Return predictability in firms with complex ownership network - GONZALEZ, Angelica (Institutional Knowledge at Singapore Management University, 2020)
Using global cross-ownership data, we show return predictability for all four possible cases in ownership-linked firms (OLFs): subsidiary-parent, parent-subsidiary, subsidiary-subsidiary, and parent-parent. A long/short portfolio strategy sorted by the lagged monthly returns of OLFs yields monthly Fama-French six-factor alpha of 79-113 bps. These results are not subsumed by customer-supplier relations, industry or cross-country return momentums. The return predictability in OLFs is best explained by active internal capital markets – a mechanism unique to firms with complex ownership.